The Gender and Intergenerational Consequences of the Demographic Dividend - Schultz, T. Paul (World Bank, 2012)
The demographic transition changes the age composition of a population, potentially affecting resource allocation at the household level and exerting general equilibrium effects at the aggregate level. If age profiles of income, consumption, and savings were stable and estimable for the entire population, they might imply how the demographic transition would affect national savings rates, but there is little agreement on the impact of age composition. These age profiles differ by gender and are affected by human capital investments, whereas existing microsimulations are estimated from samples of wage earners that are not distinguished by sex or schooling and make no effort to model family labor supply behavior or physical and human capital accumulation. Considering these shortcomings of assessments of the "demographic dividend," a case study based on household surveys and long-run social experiments may be more informative. Matlab, Bangladesh, extended a family planning and maternal and child health program to half the villages in the district in 1977, and recorded fertility in the program villages was 15–16 percent lower than in the control villages for two decades. Households in the program villages realized health and productivity gains that were concentrated among women, survival and schooling increased among children, and after 19 years household physical assets were 25 percent greater per adult than in the control villages. These large gains in the wake of the program-induced demographic transition suggest reasons for designing new labor market and microcredit policies to help women during the demographic transition invest in productive skills; shift their time more efficiently from child care to home production, self-employment, and wage labor; and invest more in the human capital of their children.